Effectiveness of Using Cellular Phones to Transmit Real-Time Shelter Morbidity Surveillance Data After Hurricane Sandy, New Jersey, October to November, 2012. (18th December 2015) - Shumate, Alice M.; Yard, Ellen E.; Casey-Lockyer, Mary; Apostolou, Andria; Chan, Miranda; Tan, Christina; Noe, Rebecca S.; Wolkin, Amy F.
Abstract: Timely morbidity surveillance of sheltered populations is crucial for identifying and addressing their immediate needs, and accurate surveillance allows us to better prepare for future disasters. However, disasters often create travel and communication challenges that complicate the collection and transmission of surveillance data. We describe a surveillance project conducted in New Jersey shelters after Hurricane Sandy, which occurred in November 2012, that successfully used cellular phones for remote real-time reporting. This project demonstrated that, when supported with just-in-time morbidity surveillance training, cellular phone reporting was a successful, sustainable, and less labor-intensive methodology than in-person shelter visits to capture morbidity data from multiple locations and opened a two-way communication channel with shelters. ( Disaster Med Public Health Preparedness . 2015;10:525–528)